Avaliação tribomecânica via esclerometria retilínea e indentação instrumentada do aço abnt 8550 - Ferreira, Fernando Martins (2010)
The ABNT 8550 steel is used for manufacturing pump rotors used in the gas and oil multiphase pumping systems. These rotors are submitted basically to erosive and abrasive wear. In order to evaluate the tribomechanical properties of quenched and tempered and annealed ABNT 8550 samples, microscratch and indentation tests were carried out. Parameters such as scratch speed, Rockwell C indenter tip radius and scratching normal load were studied. From scratch tests were obtained scratch hardness, apparent friction coefficient and specific energy. Wear mechanisms were evaluated by means of fab and scanning electron microscopy. The quenched and tempered steel showed a higher scratch hardness compared to those measured in the annealed samples. A scratch speed difference in two orders of magnitude had no significant influence on the tribological behavior for the quenched and tempered material. An increase on the indenter tip radius lead to a slightly influence on the scratch hardness for quenched and tempered samples, while for annealed steel, it resulted in a reduction of the scratch hardness. Fab values increased with an increasing indenter tip radius for both materials. Higher loads and smaller indenter tip radius lead to higher microcutting during scratch, while an increase in the normal load, when using a 50 μm tip indenter radius, resulted in a change of geometry in the scratching process. Finally, the results showed that the apparent friction coefficient increases with the reduction of the indenter tip radius. It also increased with an increasing normal load due to a scratch geometry change and increased plastic deformation. It was verified that the friction coefficient decreases with an increasing material hardness.